TALEN-Based HvMPK3 Knock-Out Attenuates Proteome and Root Hair Phenotypic Responses to flg22 in Barley - Takáč, Tomáš; Křenek, Pavel; Komis, George; Vadovič, Pavol; Ovečka, Miroslav; Ohnoutková, Ludmila; Pechan, Tibor; Kašpárek, Petr; Tichá, Tereza; Basheer, Jasim; Arick, Mark; Šamaj, Jozef (Frontiers in Plant Science, 2021)
Mitogen activated protein kinases (MAPKs) integrate elicitor perception with both early and late responses associated with plant defence and innate immunity. Much of the existing knowledge on the role of plant MAPKs in defence mechanisms against microbes stems from extensive research in the model plant Arabidopsis thaliana. In the present study, we investigated the involvement of barley (Hordeum vulgare) MPK3 in response to flagellin peptide flg22, a well-known bacterial elicitor. Using differential proteomic analysis we show that TALEN-induced MPK3 knock-out lines of barley (HvMPK3 KO) exhibit constitutive downregulation of defence related proteins such as PR proteins belonging to thaumatin family and chitinases. Further analyses showed that the same protein families were less prone to flg22 elicitation in HvMPK3 KO plants compared to wild types. These results were supported and validated by chitinase activity analyses and immunoblotting for HSP70. In addition, differential proteomes correlated with root hair phenotypes and suggested tolerance of HvMPK3 KO lines to flg22. In conclusion, our study points to the specific role of HvMPK3 in molecular and root hair phenotypic responses of barley to flg22.